
Factoring of polynomials
In general case factoring of a polynomial is not always possible. But there are some cases, when it can be executed.
1. 
If all terms of a polynomial contain as a factor the same expression, it is possible to take
it out of brackets (see above).

2. 
Sometimes grouping terms of a polynomial into brackets, one can find a common
expression inside the brackets, the expression may be taken out of the brackets as a
common factor, and after this the same expression will be inside all brackets Then this
expression must also be taken out of the brackets and the polynomial will be factored.
E x a m p l e : ax + bx + ay+ by = ( ax+ bx ) + ( ay + by ) =
= x (
a + b ) + y ( a + b ) = ( x + y ) ( a + b ) .

3. 
Sometimes including of new, mutually cancelled terms, helps to factor a polynomial.
E x a m p l e : y^{ 2} – b^{ 2} = y^{ 2}
+ yb – yb – b^{ 2} = ( y^{ 2} + yb ) – ( yb + b ^{2} ) =
= y
( y + b ) – b ( y + b ) = ( y + b ) ( y – b ) .

4. 
Usage of the formulas of abridged multiplication.

Back

